CIViCdb 2022: evolution of an open-access cancer variant interpretation knowledgebase. Issue Volume 51:Issue D1(2023) (14th November 2022) - Krysiak, Kilannin; Danos, Arpad M; Saliba, Jason; McMichael, Joshua F; Coffman, Adam C; Kiwala, Susanna; Barnell, Erica K; Sheta, Lana; Grisdale, Cameron J; Kujan, Lynzey; Pema, Shahil; Lever, Jake; et al.
Abstract: CIViC (Clinical Interpretation of Variants in Cancer; civicdb.org) is a crowd-sourced, public domain knowledgebase composed of literature-derived evidence characterizing the clinical utility of cancer variants. As clinical sequencing becomes more prevalent in cancer management, the need for cancer variant interpretation has grown beyond the capability of any single institution. CIViC contains peer-reviewed, published literature curated and expertly-moderated into structured data units (Evidence Items) that can be accessed globally and in real time, reducing barriers to clinical variant knowledge sharing. We have extended CIViC's functionality to support emergent variant interpretation guidelines, increase interoperability with other variant resources, and promote widespread dissemination of structured curated data. To support the full breadth of variant interpretation from basic to translational, including integration of somatic and germline variant knowledge and inference of drug response, we have enabled curation of three new Evidence Types (Predisposing, Oncogenic and Functional). The growing CIViC knowledgebase has over 300 contributors and distributes clinically-relevant cancer variant data currently representing >3200 variants in >470 genes from >3100 publications.